Pliocene diatom and sponge spicule oxygen isotope ratios from the Bering Sea: isotopic offsets and future directions - Snelling, Andrea M.; Swann, G.E.A.; Pike, Jennifer; Leng, Melanie J. (European Geosciences Union, 2014)
Oxygen isotope analyses of different size fractions of Pliocene diatoms (δ18Odiatom) from the Bering Sea show no evidence of an isotope offset and support the use of bulk diatom species samples for palaeoceanographic reconstructions. Additional samples containing concentrations of sponge spicules produce δ18O values several per mille (‰) lower than δ18Odiatom with a calculated mean offset of 3.9‰ ± 1.5. This difference is significantly greater than modern-day variations in water δ18O through the regional water column. Despite the potential for oxygen isotope disequilibrium within δ18Osponge, there appears to be some similarity between δ18Osponge and a global stacked benthic δ18Oforam record. This highlights the potential for δ18Osponge in palaeoenvironmental research at sites where carbonates are not readily preserved.